The pH of spray-dried blood meal does not influence nursery pig performance - Woodworth, J.C.; James, B.W.; Webster, M.J.; Real, D.E.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two studies were conducted to evaluate the effects of spray-dried blood meal and its pH on nursery pig performance. Spray-dried blood meal pH decreases as storage time increases prior to spray drying. In Exp. 1, addition of 2.5% spray-dried blood meal to the diet improved ADG and ADFI in nursery pigs (15.4 lb to 35.9 lb), but did not influence feed efficiency. In Exp. 2, the inclusion of 5% spray-dried blood meal improved feed efficiency without affecting ADG or ADFI. The pH (7.4 to 5.9 in Exp. 1 and 7.6 to 5.9 in Exp. 2) of the blood meal did not influence growth performance.
Keywords: Swine; Nursery pig; Blood meal; Growth